Walking speed differentially alters spinal loads in persons with traumatic lower limb amputation. (21st March 2018) - Hendershot, Brad D.; Shojaei, Iman; Acasio, Julian C.; Dearth, Christopher L.; Bazrgari, Babak
Abstract: Persons with lower limb amputation (LLA) perceive altered motions of the trunk/pelvis during activities of daily living as contributing factors for low back pain. When walking (at a singular speed), larger trunk motions among persons with vs. without LLA are associated with larger spinal loads; however, modulating walking speed is necessary in daily life and thus understanding the influences of walking speed on spinal loads in persons with LLA is of particular interest here. Three-dimensional trunk-pelvic kinematics, collected during level-ground walking at self-selected (SSW) and two controlled speeds (∼1.0 and ∼1.4 m/s), were obtained for seventy-eight participants: 26 with transfemoral and 26 with transtibial amputation, and 26 uninjured controls (CTR). Using a kinematics-driven, non-linear finite element model of the lower back, the resultant compressive and mediolateral/anteroposterior shear loads at the L5/S1 spinal level were estimated. Peak values were extracted and compiled. Despite walking slower at SSW speeds (∼0.21 m/s), spinal loads were 8–14% larger among persons with transfemoral amputation vs. CTR. Across all participants, peak compressive, mediolateral, and anteroposterior shear loads increased with increasing walking speed. At the fastest (vs. slowest) controlled speed, these increases were respectively 24–84% and 29–77% larger among persons with LLA relative to CTR. Over time, repeated exposures to these increased spinal loads, particularly at faster walking speeds, may contribute to the elevated risk for low back pain among persons with LLA. Future work should more completely characterize relative risk in daily life between persons with vs. without LLA by analyzing additional activities and tissue-level responses.